Penggunaan Artificial Intelligence oleh mahasiswa dalam pembelajaran - Apriliani, Yasinta (Maliki Interdisciplinary Journal, 2025)
Artificial Intelligence (AI) technology is often used to describe systems built on machines or computers that have similar or even more intelligence than humans. Only one or two AI platforms are made by humans to ease human work, but AI has many types that each platform has unique goals and features, the author wants to explain the survival platform that is often used by university students based on a survey that has been conducted by the author. The research method used is descriptive qualitative research, using data collection methodology through questions that can be answered directly by respondents following their respective answers. AI can help students with learning disabilities reach their full potential. For the emotion domain. With the help of AI, students can gain confidence in learning outcomes because AI can help learning in a fun and comfortable environment, which results in a sense of developing self-confidence and reducing anxiety associated with learning.